2019
DOI: 10.1002/app.47829
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of intrinsically flame‐retardant polyamide 6 fibers and fabrics

Abstract: In this study, flame‐retarded polyamide 6 (FR‐PA6) was prepared via the direct co‐condensation of ε‐caprolactam with two different organophosphorus compounds in a typical melt‐polymerization process. Polymer microstructures, especially the incorporation of the phosphorus‐containing comonomers, as well as the thermal and physical properties of the resulting copolyamides have been studied in detail. The phosphorus‐modified PAs have a P‐content of 0.10–0.30 wt %, possess high relative viscosities of 2.2–2.4 and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Relative viscosities were determined in H 2 SO 4 with the aid of an Ubbelohde viscosimeter. Number‐average molecular weights were determined therefrom with the aid of literature values (see SI) 49–50 . Increasing molecular weights correlate well with increasing monomer to initiator ratios.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative viscosities were determined in H 2 SO 4 with the aid of an Ubbelohde viscosimeter. Number‐average molecular weights were determined therefrom with the aid of literature values (see SI) 49–50 . Increasing molecular weights correlate well with increasing monomer to initiator ratios.…”
Section: Resultsmentioning
confidence: 99%
“…Number-average molecular weights were determined therefrom with the aid of literature values (see SI). [49][50] Increasing molecular weights correlate well with increasing monomer to initiator ratios. Although the values found by this method are in good accordance with the stoichiometry, they still represent estimated values and should not be used as exact but, instead, as qualitative measures.…”
Section: Solidification Timesmentioning
confidence: 92%
“…In line with the higher activator content, melting points ( T m ) of the resulting PA6 are somewhat lower (205–215 °C) than the one of PA6 prepared by anionic polymerization ( T m ≈ 220 °C). [ 49 ] Indeed, the reaction solidified in an acceptable time span with quantitative polymer yield even in the absence of CLA‐Ac (Table 2, entry 3).…”
Section: Methodsmentioning
confidence: 99%
“…The presence of phosphorus groups in the structure of this textile was the main reason of its flame-retardant ability. Moreover, it was shown that the presence of the organophosphorus compounds in the structure of polyamide had no negative effect on its other features (Mourgas et al 2019).…”
Section: Flame-retardant Textilesmentioning
confidence: 99%